Elucidation of the Host Bronchial Lymph Node miRNA Transcriptome Response to Bovine Respiratory Syncytial Virus - Johnston, Dayle; Earley, Bernadette; McCabe, Matthew S.; Kim, Jaewoo; Taylor, Jeremy F.; Lemon, Ken; McMenamy, Michael; Duffy, Catherine; Cosby, S. Louise; Waters, Sinéad M. (Frontiers in Genetics, 2021)
Bovine Respiratory Disease (BRD) causes morbidity and mortality, affecting cattle of all ages. A main cause of BRD is an initial inflammatory response with Bovine Respiratory Syncytial Virus (BRSV). MicroRNAs are non-coding small RNAs that regulate many biological processes and are implicated in various inflammatory diseases. The objective of this study was to elucidate changes in the bovine bronchial lymph node miRNA transcriptome in response to BRSV following an experimental viral challenge. Holstein-Friesian calves were either administered a challenge dose of BRSV (103.5 TCID50/ml × 15 ml) (n = 12) or were mock inoculated with sterile phosphate buffered saline (n = 6). Daily scoring of clinical signs was performed and calves were euthanised at day 7 post-challenge. Bronchial lymph nodes were subjected to RNA extraction and sequencing (75 bp). Read counts for known miRNAs were generated using the miRDeep2 package using the UMD3.1 reference genome and the bovine mature miRNA sequences from the miRBase database. EdgeR was used for differential expression analysis and Targetscan was used to identify target genes for the differentially expressed (DE) miRNAs. Target genes were examined for enriched pathways and gene ontologies using Ingenuity Pathway Analysis. Multi-dimensional scaling based on miRNA gene expression changes, revealed a separation between the BRSV challenged and control calves, although the clinical manifestation of disease was mild. One hundred and nineteen DE miRNAs (P < 0.05, FDR < 0.1, fold change > 1.5) were detected between the BRSV challenged and control calves. DE miRNAs were predicted to target 465 genes previously found to be DE in bronchial lymph node tissue, between these BRSV challenged and control calves. Of the DE predicted target genes, 455 had fold changes that were inverse to the corresponding DE miRNAs. There were 8 enriched pathways among the DE predicted target genes with inverse fold changes to their corresponding DE miRNA including: granulocyte and agranulocyte adhesion and diapedesis, interferon signalling and role of pathogen recognition receptors in recognition of bacteria and viruses. Functions predicted to be increased included: T cell response, apoptosis of leukocytes, immune response of cells and stimulation of cells.